Functional versus conventional strength and conditioning programs for back injury prevention in emergency responders - Kong, Pui Wah; Kan, Tommy Yew Weng; Mohamed Jamil, Roslan Abdul Ghani Bin; Teo, Wei Peng; Pan, Jing Wen; Hafiz Abd Halim, Md Noor; Abu Bakar Maricar, Hasan Kuddoos; Hostler, David (Frontiers in Bioengineering and Biotechnology, 2022)
Back pain and back-related injuries are common complaints among emergency responders. The purpose of this study was to compare the effectiveness of two strength and conditioning programs in improving back muscle characteristics and disabilities in emergency responders (firefighters/paramedics). Participants (n = 24) were randomized into two groups to complete 16 weeks of supervised exercise intervention: 1) Functional training used unilateral movements that mimicked the asymmetrical nature of emergency operations, 2) Conventional training performed bilaterally loaded exercises. Outcome measures were maximum isometric back extension strength, passive muscle stiffness, lumbar extensor fatigability, and revised Oswestry Low Back Pain Questionnaire. A mixed model Analysis of Variance with repeated measures was performed to compare the difference over time and between groups. While the training effects were similar between groups, both programs improved isometric back extension strength (+21.3% functional, +20.3% conventional, p < .001, η²p = 0.625) and lumbar extensor muscle fatigability (+17.4% functional, +9.5% conventional, p = .009, η²p = 0.191). Bilateral symmetry in muscle stiffness was improved as indicated by reduction in symmetry index (-7.1% functional, -11.8% conventional, p = .027, η²p = 0.151). All self-reported pain and disability scores fell within the category of “minimum functional limitation” throughout the intervention and 6-month follow-up periods. For frontline firefighters and paramedics, both functional and conventional strength training are effective for improving back muscle characteristics.